The spectrum of GERD implications for assessment and management - Quigley, Eamonn M. M. (Henry Stewart Talks, 2011)
What is GERD, NERD non-erosive reflux disease, Predictors of NERD vs. ERD, Mechanisms of symptom production in NERD, Functional heartburn, Predictors of functional heartburn vs. pH + NERD, Factors leading to the development of symptoms in GERD patients, Role of DGER in "resistant" GERD, NERD: management issues, The limits of GERD, Progression in ProGERD, Extra-esophageal, supra-esophageal GERD, Laryngitis, Cough and GERD, Asthma and GERD, Scleroderma and GERD, The Barrett's dilemma, Risk factors for Barrett's and adenocarcinoma, Genetic markers that can predict progression, Barrett's management issues, GERD management issues